Pariwisata Halal Indonesia: Kajian Literatur Review Menggunakan Protokol SPAR-4-SLR dan Analisis TCCM - Muhammad, Fahmi; Yusrizal, Firdaus; Nawawi, Ahmad; Nurita, Riau; Yulia, Nur Arini (Sekolah Vokasi, Universitas Gadjah Mada, 2025)
Halal tourism has emerged as a significant global phenomenon in line with the growing population of Muslim travelers worldwide. This development has spurred a rapid increase in academic studies related to halal tourism, particularly over the past decade. However, the application of a Systematic Literature Review (SLR) using the SPAR-4-SLR protocol remains limited, especially on the specific topic of halal tourism in the Indonesian context. This study aims to examine the trends and development of halal tourism research in Indonesia by employing the SLR method in conjunction with the TCCM (Theory, Context, Characteristic, Method) analytical framework. The research was conducted in two main stages, first the application of the SPAR-4-SLR protocol to identify and screen relevant literature and, second a detailed analysis using the TCCM framework. The assembling stage identified 112 relevant articles, which were then narrowed down to 50 key articles during the arranging stage for indepth analysis in the assessing phase. The findings reveal that theoretically halal tourism research remains centered on marketing and customer satisfaction issues, with limited exploration of sociocultural aspects and information technology. In terms of context, studies predominantly focus on Muslim-majority regions, while non-Muslim areas with high tourism potential remain underexplored. Regarding characteristics, correlational and causal approaches dominate, primarily examining relationships between halal tourism and other sectors or themes. Methodologically, quantitative approaches particularly Structural Equation Modeling using Partial Least Squares (SEM-PLS) are the most commonly applied, whereas mixed methods and longitudinal studies are still relatively scarce. These findings offer valuable insights into mapping the direction and research gaps in halal tourism studies in Indonesia moving forward.